Pengaruh Media Pembelajaran Ular Tangga Berbasis Digital terhadap Hasil Belajar IPAS Peserta Didik Kelas IV SD Negeri Joglo 76 Surakarta - Desi Ratna Sari; Oktiana Handini; Jumanto Jumanto (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study investigates the impact of digital-based snake and ladder learning media on student achievement in Science and Social Science (IPAS) subjects among fourth-grade students at SD Negeri Joglo 76 Surakarta. The research employed a quantitative approach with a quasi-experimental design, utilizing a pretest-posttest control group model. A total of 53 students participated, divided into two groups: the experimental group, which used digital snake and ladder media integrated with Problem-Based Learning (PBL), and the control group, which received instruction through conventional PBL methods. Data collection involved written tests, interviews, observation, and documentation. Statistical analysis using an independent sample t-test indicated a significant difference in learning outcomes between the two groups, demonstrating the effectiveness of digital game-based learning. The findings suggest that integrating interactive digital media enhances motivation, engagement, and academic performance in primary education settings.